Occurrence, biological activity and synthesis of drimane sesquiterpenoids - Jansen, B. J. M.; de Groot, Ae (Natural product reports, 2004)
In this review the names, structures and occurrence of all new drimanes and rearranged drimanes which have been published between January 1990 and January 2003 have been collected. Subjects that have been treated are biosynthesis, analysis, biological activities, with special attention to cytotoxic activity and antifeedant and insecticidal activity and mode of action. An important part of the review deals with the synthesis of drimanes. This part has been subdivided into syntheses by transformation of natural products, syntheses starting from chiral compounds obtained by enzymatic resolution, syntheses by cationic polyolefin cyclizations, syntheses from trans-decalones, syntheses by radical cyclizations and syntheses by cycloaddition reactions. The review contains about 350 references.